What makes a good parent? Sex-specific relationships between nest attendance, hormone levels, and breeding success in a long-lived seabird. (31st May 2017) - Riechert, Juliane; Becker, Peter H.
Abstract: Biparental care is found across taxa, but sex-specific contributions vary greatly both between and within species. Factors underlying intraspecific variation may include the phase of the reproductive cycle and sex-specific duties resulting in physiological or environmental constraints that differ between the sexes. For pair members to achieve high breeding success while maintaining good condition, parental duties should be well coordinated between mates. Avian breeding behavior is mediated by hormones such as prolactin and corticosterone, which link the internal and environmental parameters of individuals and regulate resource allocation. Using automated recording at the nest, we analyzed parental attendance by Common Terns ( Sterna hirundo ) in relation to sex, reproductive phase (incubation, chick rearing), time of day, breeding experience, and hormone levels, and related it to reproductive success. Nest attendance of females exceeded that of males, especially at night and during chick rearing. Greater breeding experience was linked to increased attendance at night by males and during incubation by females. Parental nest attendance during incubation was not related to duration of the incubation phase, nor to hatching success. However, fledging success increased with greater parental attendance during the early chick rearing period, reflecting a higher vulnerability of small chicks to mortality compared with eggs. Prolactin values of male parents were significantly lower during chick rearing than incubation and in comparison with values of female parents. Female breeding experience was positively correlated with increased hormone values during chick rearing. Male attendance during chick rearing covaried with hormone levels: moderately increased corticosterone could support males in their new role as feeders by facilitating high activity and foraging effort, whereas lowered prolactin might indicate less contact with chicks and reduced body weight. We show that Common Terns exhibit a flexible system of sex-specific parental care during incubation and chick rearing, reflected in hormone levels, which mediate breeding behavior and ultimately affect reproductive success.